2021
DOI: 10.1080/22221751.2021.1965497
|View full text |Cite
|
Sign up to set email alerts
|

Novel murine models for studying Cache Valley virus pathogenesis and in utero transmission

Abstract: Cache Valley virus (CVV) is a prevalent emerging pathogen of significant importance to agricultural and human health in North America. Emergence in livestock can result in substantial agroeconomic losses resulting from the severe embryonic lethality associated with infection during pregnancy. Although CVV pathogenesis has been well described in ruminants, small animal models are still unavailable, which limits our ability to study its pathogenesis and perform preclinical testing of therapeutics. Herein, we exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…al (2021) showed that IFN plays an important role in disease of CVV in vivo . Similar to our results, six-week-old IFN-αβR -/- mice inoculated subcutaneously with 10 4 PFU of CVV became moribund by eight days post-infection [ 34 ]. Our previous studies have shown that the lack of α/β and γ IFN receptors in AG129 mice and subsequent downregulated IFN responses results in susceptibility to a host of other arboviruses [ 27 , 35 38 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…al (2021) showed that IFN plays an important role in disease of CVV in vivo . Similar to our results, six-week-old IFN-αβR -/- mice inoculated subcutaneously with 10 4 PFU of CVV became moribund by eight days post-infection [ 34 ]. Our previous studies have shown that the lack of α/β and γ IFN receptors in AG129 mice and subsequent downregulated IFN responses results in susceptibility to a host of other arboviruses [ 27 , 35 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…AG129 mice have also been used to investigate sexual transmission and teratogenicity of Zika virus, another arbovirus of public health concern [ 39 ]. Likewise, pregnant IFN-αβR -/- mice have been used to study CVV vertical transmission resulting in spontaneous abortions and congenital malformations in vivo [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma samples were not collected. Mice were immediately euthanized when moribund or upon weight loss greater than or equal to 20% of their original body weight, as previously described 11,12 …”
Section: Methodsmentioning
confidence: 99%
“…Outbred ICR mice were resistant to CVV infection and viral-induced teratogenicity in pregnant mice (Edwards et al 1998). However, interferon receptor-deficient mice are susceptible to CVV infection via peripheral routes of inoculation and vertical transmission of the virus resulting in spontaneous abortions and congenital malformations (Lopez et al 2021, Skinner et al 2022). The lack of an effective interferon response in these mice leading to productive CVV infections is not surprising given that interferon has been shown to play an essential role in restricting growth of orthobunyavirids, including CVV and La Crosse virus (Hefti et al 1999, Kochs et al 2002, Rodrigues Hoffmann et al 2013).…”
Section: Clinical Disease In Animalsmentioning
confidence: 99%